The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.3389/fmicb.2015.01227
|View full text |Cite
|
Sign up to set email alerts
|

An insight into the isolation, enumeration, and molecular detection of Listeria monocytogenes in food

Abstract: Listeria monocytogenes, a foodborne pathogen that can cause listeriosis through the consumption of food contaminated with this pathogen. The ability of L. monocytogenes to survive in extreme conditions and cause food contaminations have become a major concern. Hence, routine microbiological food testing is necessary to prevent food contamination and outbreaks of foodborne illness. This review provides insight into the methods for cultural detection, enumeration, and molecular identification of L. monocytogenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
70
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(73 citation statements)
references
References 150 publications
2
70
0
1
Order By: Relevance
“…Listeria monocytogenes is one the most habitually investigated foodborne pathogens, whereas the L. monocytogenes outbreaks had the highest proportion of hospitalized cases as well as the highest proportion of deaths registered in the European Union (Anonymous, 2011; Law et al, 2015a). Flekna et al (2007b) combined EMA with qPCR to detect viable cells of C. jejuni and L. monocytogenes .…”
Section: Ema/pma In Differentiation Of Viable Cells Of Listeria Monocmentioning
confidence: 99%
“…Listeria monocytogenes is one the most habitually investigated foodborne pathogens, whereas the L. monocytogenes outbreaks had the highest proportion of hospitalized cases as well as the highest proportion of deaths registered in the European Union (Anonymous, 2011; Law et al, 2015a). Flekna et al (2007b) combined EMA with qPCR to detect viable cells of C. jejuni and L. monocytogenes .…”
Section: Ema/pma In Differentiation Of Viable Cells Of Listeria Monocmentioning
confidence: 99%
“…Cultures which do not turn black can be considered free of Listeria spp., and further analysis may be unnecessary. However, potential negative results with Fraser broth can occur and as a result, it is advised to plate all cultures for further analysis [6,13]. In this study, the result shown in Fraser broth was further confirmed using PCR.…”
Section: Discussionmentioning
confidence: 68%
“…Bacterial cell-surface lipopolysaccharides are ligands for TLR1 activation (48), whereas TLR10 has been suggested as a key mediator of Listeria monocytogenes-induced inflammation (49). L. monocytogenes has become a major foodborne pathogen that can be found in meat and processed foods due to its ability to survive the most common food-processing conditions such as extreme pH, high salt concentration, low water activity, and refrigeration temperatures (50). In particular, L. monocytogenes has been found in high percentages of ready-to-eat processed meat products (51-53).…”
Section: Discussionmentioning
confidence: 99%